Let’s Talk: Starting Conversations with Parents and Teachers on their Beliefs in Education - Markovich Morris, Emily; Winthrop, Rebecca (International Journal about Parents in Education, 2023)
Over the past decade, schools around the world have had to develop educational strategies to respond to pressing health, environmental, social, economic, and political emergencies and situations. A critical concern for education leaders is how to develop educational strategies that are responsive to and inclusive of families and communities. This article presents a methodology for facilitating conversations between families and schools that leads to recommendations for improving family, school, and community engagement. This methodology starts with surveying teachers’ and families’ beliefs on teaching and learning. Survey data on beliefs in seven countries are analyzed. Beliefs are then used to launch conversations between teachers, parents/caregivers, and community representatives, using a dialogical approach. A case study of this conversation process carried out in Colombia is presented. The parent/caregiver and teacher conversations not only led to new school and regional strategies, but helped teams confront power dynamics, a vital step in transforming education systems.